Adenovirus Encoded Adjuvant (AdEnA) anti-CTLA-4, a novel strategy to improve Adenovirus based vaccines against infectious diseases and cancer - D’Alise, Anna Morena; Nocchi, Linda; Garzia, Irene; Seclì, Laura; Infante, Luigia; Troise, Fulvia; Cotugno, Gabriella; Allocca, Simona; Romano, Giuseppina; Lahm, Armin; Leoni, Guido; Sasso, Emanuele; et al. (Frontiers in Immunology, 2023)
Introduction: Virus vectored genetic vaccines (Vvgv) represent a promising approach for eliciting immune protection against infectious diseases and cancer. However, at variance with classical vaccines to date, no adjuvant has been combined with clinically approved genetic vaccines, possibly due to the detrimental effect of the adjuvant-induced innate response on the expression driven by the genetic vaccine vector. We reasoned that a potential novel approach to develop adjuvants for genetic vaccines would be to “synchronize” in time and space the activity of the adjuvant with that of the vaccine. Methods: To this aim, we generated an Adenovirus vector encoding a murine anti-CTLA-4 monoclonal antibody (Ad-9D9) as a genetic adjuvant for Adenovirus based vaccines. Results: The co-delivery of Ad-9D9 with an Adeno-based COVID-19 vaccine encoding the Spike protein resulted in stronger cellular and humoral immune responses. In contrast, only a modest adjuvant effect was achieved when combining the vaccine with the same anti-CTLA-4 in its proteinaceous form. Importantly, the administration of the adjuvant vector at different sites of the vaccine vector abrogates the immunostimulatory effect. We showed that the adjuvant activity of Ad-α-CTLA-4 is independent from the vaccine antigen as it improved the immune response and efficacy of an Adenovirus based polyepitope vaccine encoding tumor neoantigens. Conclusions: Our study demonstrated that the combination of Adenovirus Encoded Adjuvant (AdEnA) with an Adeno-encoded antigen vaccine enhances immune responses to viral and tumor antigens, representing a potent approach to develop more effective genetic vaccines.